2007
DOI: 10.1007/s00383-006-1847-9
|View full text |Cite
|
Sign up to set email alerts
|

Adriamycin mouse model: a variable but reproducible model of tracheo-oesophageal malformations

Abstract: A spectrum of tracheo-oesophageal malformations is seen in humans: oesophageal atresia, tracheal agenesis and laryngotracheo-oesophageal clefts. They are thought to share a common but unknown aetiology. These birth defects are frequently associated with other VACTERL anomalies. The adriamycin rat model (ARM) has proved to be a valuable model of the VACTERL anomalies, illustrating the dysmorphogenesis of oesophageal atresia and tracheal agenesis. As organogenesis relies on temporaspatially co-ordinated signalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…The Adriamycin rat model, which has also been adapted to the mouse, is a teratogenic model of EA/TEF (Diez-Pardo et al, 1996;Dawrant et al, 2007). Adriamycin is a glycosidic anthracycline antibiotic, which is used in chemotherapy.…”
Section: Experimental Teratogenic Modelmentioning
confidence: 99%
“…The Adriamycin rat model, which has also been adapted to the mouse, is a teratogenic model of EA/TEF (Diez-Pardo et al, 1996;Dawrant et al, 2007). Adriamycin is a glycosidic anthracycline antibiotic, which is used in chemotherapy.…”
Section: Experimental Teratogenic Modelmentioning
confidence: 99%
“…The mouse is the foremost mammalian model of development, offering an expanding wealth of genetic and molecular knowledge and scientific research techniques. Our group has confirmed that the Adriamycin mouse model (AMM) produces a spectrum of tracheo-oesophageal malformations [5,6].…”
Section: Introductionmentioning
confidence: 54%
“…Dawrant et al [53] reported that the administration of an increased dose of Adriamycin of 6 mg/kg induced foregut and notochord anomalies in 64% of exposed embryos. The notochord was identical to that seen in the ARM, in that similarly in the mouse the administration of Adriamycin seems to cause a prolonged and abnormal adhesion between the endoderm and notochord (Figs.…”
Section: The Mouse Modelmentioning
confidence: 98%